Penyuluhan Pola Hidup Sehat Dan Literasi Digital Bagi Pelajar Desa Tarikolot Untuk Meningkatkan Kesadaran Teknologi - Bani Nurhakim; Cep Lukmanrohmat; Aziz Alma’as; Muhamad Yoni Ardiansah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This community service program aims to increase awareness of healthy living habits and digital literacy among students in Tarikolot Village as an effort to improve their well-being and readiness to face challenges in the digital era. Based on initial observations, students in Tarikolot Village still have unhealthy eating habits, lack physical activity, and pay little attention to personal and environmental hygiene. In addition, the use of digital technology among students is still limited to entertainment, such as playing games and accessing social media, without understanding the positive potential and risks of using technology wisely. This program was implemented through interactive counseling, hands-on practice, simulations, and mentoring. The material presented in this activity includes health education such as the importance of balanced nutrition, personal hygiene, and physical activities. Meanwhile, the digital literacy materials cover safe internet usage, ethics in social media, hoax identification, and utilizing technology for learning and digital economic opportunities. The results of this program indicate an increase in students' understanding and behavioral changes. Around 80% of participants began to implement healthy habits such as proper handwashing, choosing nutritious foods, and engaging in regular physical activity. In addition, participants became wiser in using social media, were able to identify hoaxes, and started utilizing the internet for productive purposes such as online learning. The outcomes of this program include educational modules on healthy living and digital literacy, educational videos, infographics, and certificates for participants. This program is expected to create a young generation that is healthy, smart, and wise in using technology so that they can face the challenges of the digital era more effectively and responsibly.